2017
DOI: 10.1128/genomea.00562-17
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Zymomonas mobilis subsp. mobilis NRRL B-1960

Abstract: Zymomonas mobilis subsp. mobilis is an efficient ethanol producer with application for industrial production of biofuel. To supplement existing Z. mobilis genomic resources and to facilitate genomic research, we used Oxford Nanopore and Illumina sequencing to assemble the complete genome of the beer spoilage isolate Z. mobilis subsp. mobilis strain NRRL B-1960.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…mobilis NRRL B-1960 plasmid sequence of pZMO1960-1A is identical to the Z . mobilis NCIMB 11163 plasmid pZMO1A, which the complete genome sequences were most closely related between these strains[ 16 ].The sequences of plasmids pZZM401, pZM1252603 pZM1402303,pAZ1001,pZMOB04 and pZMOB05 were relatively similar. However, the plasmid sequences of Z .…”
Section: Resultsmentioning
confidence: 99%
“…mobilis NRRL B-1960 plasmid sequence of pZMO1960-1A is identical to the Z . mobilis NCIMB 11163 plasmid pZMO1A, which the complete genome sequences were most closely related between these strains[ 16 ].The sequences of plasmids pZZM401, pZM1252603 pZM1402303,pAZ1001,pZMOB04 and pZMOB05 were relatively similar. However, the plasmid sequences of Z .…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate multi-omic data analyses, the genomes of eight Z. mobilis strains have been completely sequenced, including model strain ZM4 [ 17 23 ]. In 2009, we improved the genome annotation of Z. mobilis ZM4 (AE008692.2) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative genome assembly size ranged from 2.07 to 2.49 Mb, with GC content ranging from 32 to 36%. Using the PhAME pipeline 39 , we identified 74,825 polymorphic sites between the genomes of the three Z. mobilis strains from pulque and an additional 7 previously sequenced Z. mobilis genomes [40][41][42][43][44][45] . Phylogenetic analysis revealed that the pulque isolates we sequenced were monophyletic with a previously sequenced strain ATCC 10988, which was also isolated from pulque (Fig.…”
Section: Taxonomic Profiling Of Microbial Community During Pulque Fermentioning
confidence: 99%
“…We used the PhaME package 39 to identify single nucleotide polymorphisms between seven publicly available Z. mobilis genomes and the three Z. mobilis genome we isolated from pulque. Strains extracted from the NCBI database included (strain (GenBank accession number)): ATCC31821 (ASM710v1), ATCC10988 (ASM17525v2), ATCC29191 (ASM27775v1), NRRL B-14023 (ASM57616v1), NRRL B-12526 (ASM57612v1), NRRL B-1960 (ASM215884v1), NCIMB 11163 (ASM2424v1) [40][41][42][43][44][45] . We used the ATCC31821 genome as the reference during PHaME analysis.…”
Section: Statistical Analysis and Data Visualizationmentioning
confidence: 99%